Dampak Karies Gigi Terhadap Kualitas Hidup Anak - Velya Apro; Susi Susi; Desy Purnama Sari (Andalas Dental Journal, 2020)
Caries is one of the most common dental and oral health problems in the world and attacks all ages. According to WHO in 2016 the prevalence of caries in school children is 60-90%. Caries affects the disruption of children's activities and will have an impact on the quality of life. The quality of life is an individual perceptions of physical, psychological, social, and environmental conditions in someone daily life. Purpose: to review the impact between caries and children's quality of life using an instrument. The caries assessments we used are DMF-T/dmft index, PUFA/pufa, and the Caries Assessment Spectrum and Treatment Index and the quality of life assessment instrument is the Child Perceptions Questionnaire. Results: The results of the literature review show that caries has an impact on daily activities that will effect on the quality of life of the children, where children with dental caries have a worse quality of life than children without caries. Based on the Child Perception Questionnaire instrument, the negative impact of caries are oral symptoms, functional limitation, emotional well-being and social well-being. Conclusion: The impact by the child can